Legal analysis of the settlement of the criminal act of absence without permission according to Military Criminal Law and Military Disciplinary Law - Bagus Triawan (Annals of Justice and Humanity, 2023)
Purpose: This paper examines two main problems: 1) How is the article on the crime of unauthorized absence in military criminal law, and 2) How is the crime of unauthorized absence according to military criminal law and its comparison with military disciplinary law. Research Methodology: This study uses a normative legal method with a focus on legislation and case studies. Results: The results of the study show that the crime of unauthorized absence which is included in the provisions of military criminal law, namely absence without permission for a maximum of four days during peacetime, turns out to result in the failure to achieve the tasks and interests of the unit and causes unrest in the unit, so it must be resolved according to the military criminal procedure law mechanism to be examined and tried in a military court. Meanwhile, the crime of absence without permission of no more than four days in peaceful conditions if it does not impact the interests of the service and does not interfere with the achievement of unit tasks and does not cause problems in unit development, then it is sufficient to be resolved through military disciplinary law by considering the element of error in the perpetrator.